Wet and dry bacterial spore densities determined by buoyant sedimentation. - Tisa, L S (1982)
The wet densities of various types of dormant bacterial spores and reference particles were determined by centrifugal buoyant sedimentation in density gradient solutions of three commercial media of high chemical density. With Metrizamide or Renografin, the wet density values for the spores and permeable Sephadex beads were higher than those obtained by a reference direct mass method, and some spore populations were separated into several density bands. With Percoll, all of the wet density values were about the same as those obtained by the direct mass method, and only single density bands resulted. The differences were due to the partial permeation of Metrizamide and Renografin, but not Percoll, into the spores and the permeable Sephadex beads. Consequently, the wet density of the entire spore was accurately represented only by the values obtained with the Percoll gradient and the direct mass method. The dry densities of the spores and particles were determined by gravity buoyant sedimentation in a gradient of two organic solvents, one of high and the other of low chemical density. All of the dry density values obtained by this method were about the same as those obtained by the direct mass method.